2005
DOI: 10.1038/sj.cgt.7700878
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy of AAV-mediated systemic delivery of interferon-β

Abstract: Type I interferons (a/b) have significant antitumor activity although their short half-life and systemic side effects have limited their clinical utility. An alternative dosing schedule of continuous, low-level delivery, as is achieved by gene therapy, rather than intermittent, high concentration pulsed-dosing, might avoid the toxicity of interferon while maintaining its antitumor efficacy. We have tested a gene therapy approach in murine tumor models to treat malignancies that have shown responsiveness to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…3B and C). The mean endothelial cell density, as assessed by CD34 staining, was unchanged in treated U87 tumors (14,816 . To help distinguish perivascular cells from activated fibroblasts, both of which can be detected by aSMA staining, additional sections from control and IFN-h -treated tumors (four each) were stained with an anti -platelet-derived growth factor receptor h (PDGFRh) antibody because PDGFRh + cells within tumors have previously been shown to be perivascular cells (21).…”
Section: Alterations Of the Intratumoral Vasculature With Aav Ifn-b Mmentioning
confidence: 86%
See 1 more Smart Citation
“…3B and C). The mean endothelial cell density, as assessed by CD34 staining, was unchanged in treated U87 tumors (14,816 . To help distinguish perivascular cells from activated fibroblasts, both of which can be detected by aSMA staining, additional sections from control and IFN-h -treated tumors (four each) were stained with an anti -platelet-derived growth factor receptor h (PDGFRh) antibody because PDGFRh + cells within tumors have previously been shown to be perivascular cells (21).…”
Section: Alterations Of the Intratumoral Vasculature With Aav Ifn-b Mmentioning
confidence: 86%
“…These cell lines were chosen because they are only moderately sensitive to the direct cytotoxic effects of IFN-h (14,15). Treatment was initiated with administration of either AAV IFN-h or a control AAV encoding human clotting factor IX (FIX) via the tail vein, after established disease had been documented either by palpation (subcutaneous tumors) or by ultrasonography (retroperitoneal tumors).…”
Section: Restricted Growth Of Established Tumors With Aav Ifn-b Monotmentioning
confidence: 99%
“…36 Targeting PC by molecular abnormality remains elusive because of the accumulation of multiple genetic changes during its multistep carcinogenesis. During the last decade, numerous studies illustrated the gene transfer or systemic delivery of IFN-b to inhibit tumor growth in multiple animal models from gliomas, 37 to hepatocellular carcinoma, 38 metastatic breast cancer, 39 prostate cancer, [40][41][42] rectum, colon and endometrial tumors, [43][44][45] lung tumors, 46,47 renal cell carcinomas and melanoma, 48,49 neuroblastoma, 50,51 disseminated peritoneal cancer, 52 bladder cancer, 53 malignant mesothelia 54 and fibrosarcomas. 55 Recently, a cancer gene therapy trial for gliomas based on the intratumoral administration of IFN-b) was shown to be feasible and associated with apoptosis induction.…”
Section: Lentiviral Vectors For Pc Therapy E Ravet Et Almentioning
confidence: 99%
“…A variety of gene therapy-based anticancer strategies have been tested in animal tumor models, including selective activation of prodrugs, genetic immunotherapy, antiangiogenic actions and replacement of tumor suppressor genes (Sangro et al, 2002;Borghouts et al, 2005;Cao et al, 2010), successful of these approaches was depend on efficient gene transfer process, numerous gene transfer vectors have been developed, most of these approaches have used retroviral vector producer, naked DNA, oligodendromer DNA coatings, electroporation or adenoviral vectors (Qian et al, 2000;Cross et al, 2006). However, retroviral vector producers may be impractical for human use due to low titer of the vector, and the transfer of naked DNA is typically an inefficient, transient process; adenoviralmediated gene transfer is also complicated by transient (Streck et al, 2006). Adeno-associated virus (AAV) is a recently identified, nonpathogenic, helper-dependent member of the parvovirus family and becoming a promising alternative in cancer gene therapy which offer some potential advantages for gene transfer as compared to other gene delivery systems just mentioned.…”
Section: Introductionmentioning
confidence: 99%